Economy-wide effects of a major increase in the wholesale price of electricity: New Results from the JOANNA Model - Bertram, L.G (School of Management Working Papers, 1993)
This paper has reported the results of work which used a recently-updated version of the JOANNA model to repeat and extend the 1985 BERL study of the economy-wide implications of a 25% electricity price shock. The 1985 findings were successfully replicated with the exception of the government budget balance, which emerged stronger in the 1992 results rather than weaker as in the 1985 study. This sign reversal is attributed to the increased importance of indirect taxes (including GST) in the composition of government revenue, and the resulting reduced impact of GDP changes on the budget balance. The paper explored separately the two issues of price competitiveness and disposable-income effects and describes the results of the new work.